The human factor in social capital management the owner-manager perspective - Manning, Paul C. (Emerald, 2015)
This book is about the management of social capital processes as they are accomplished-understood, experienced and shaped-by owner-managers. The aim of the book is to develop a deeper understanding of these management processes, and thereby to contribute to a greater congruence between lived social capital perspectives and experiences, and theoretical and empirical literature. The book argues that social capital processes are context dependent and hence cannot be fully understood within an economic understanding of rationality. It follows that claims for the universality of the economic way of looking at life, and for looking at social capital processes are over-stated. Predicated on this insight the book investigates economic notions of rationality, as well as other perspectives on rationality in the management of social capital processes.
Keywords: Social responsibility of business.; Social capital (Sociology); Industrial management -- Moral and ethical aspects.; Business ethics.; elektronické knihy; electronic books